Associations between commuting and well-being in the context of a compact city with a well-developed public transport system. (June 2019) - Sha, Feng; Li, Bingyu; Law, Yik Wa; Yip, Paul S.F.
Abstract: Introduction: Negative impacts of long commuting time on people's well-being have been found in many suburbanized private car-dominant cities. However, there is a dearth of evidence regarding this association in a compact city with a well-developed public transport system. Taking Hong Kong as an example, the current study aims to explore the associations between modes of transport and commuting time with well-being. Methods: The study used the data of 990 commuters from the first wave of the Hong Kong Panel Survey for Poverty Alleviation in 2015. Multivariate logistic and linear regressions were used to test the associations of commuting time and commuting modes with well-being. The well-being outcomes included obesity measured by self-reported body mass index (BMI), mental distress (CHQ-12), self-rated health (SRH) and satisfaction with life (SWLS-5). Results: After the confounding variables were adjusted, significant association have been found between commuting time and satisfaction with life [-0.14, 95% CI: (−0.03, −0.00)]. More specifically, those who commute 60–89 min [-1.57, 95% CI: (−2.98, −0.16)], 90–119 min [-2.36, 95% CI (−4.56, −0.16)] and 120 min or more [-4.85, 95% CI (−9.11, −0.59)] report significantly lower satisfaction with life than those who commute within 30 min. Moreover, excessive commuting time (90–119 min) has been found significantly associated with obesity with an odd ratio of 2.80 [95% CI: (1.30–6.04)]. Conclusions: In Hong Kong, commuting time over 60 min is associated with negative satisfaction with life, and commuting time over 90 min is associated with higher risk of obesity. Policymakers of a compact city with a well-developed transport system should be informed of the negative impacts of long commuting time on well-being. Highlights: Commuting time over 60 min is associated with negative satisfaction with life. Commuting time over 90 min is associated with higher risk of obesity. Commuting mode is not associated with all the well-being outcome. Policy-makers of compact city like Hong Kong should be informed of the negative impact of long commuting time on well-being.